Counteraction to sabotage measures on ammunition depots in the context of hybrid warfare (Law and Safety, 2018)
The state of the military sector is one of the most important indicators of the state’s development, it also determines the level of influence of the country on the economic and political situation that is taking place on the international scene. Ensuring the proper state of Ukraine’s national security is accompanied not only by the mentioned factors, but also by the fact that our state is in a military conflict with the Russian Federation. The article is focused on studying the issues related to the nature of the modern hybrid warfare in Ukraine, an act of sabotage was considered as one of the ways of such a war, it analyzed the acts of sabotage, the object of which is ammunition depots placed on the territory of Ukraine. The suggestions for improving and refining the system of counteraction to acts of sabotage are provided.The topic of the study is relevant, therefore, it requires detailed consideration and study of the hybrid warfare’s nature, which combines not only conventional combat operations, but also political, economic, information, cybernetic means of combating the enemy. In the context of the military conflict, where Ukraine is located, the issue of counteracting and combating actions of sabotage, which is understood as an act aimed at weakening the state of explosions, arson, or other actions aimed at mass destruction of people, causing bodily harm or other harm to their health, destruction or damage of objects that have an important national or defense significance, etc. In our study, particular attention is paid to such objects as stockpiles of ammunition, where weapons, missiles, ammunition, explosives, firearms, special means are stored.The authors of the article offer the main ways of improving and reforming the security system of these objects. The highlighted problems and suggested ways for their solution can become the fundamental basis for the development of a new security strategy.
Keywords: act of sabotage; military objects; hybrid warfare; ammunition depots; national security